2017
DOI: 10.3390/md15110344
|View full text |Cite
|
Sign up to set email alerts
|

5-Alkylresorcinol Derivatives from the Bryozoan Schizomavella mamillata: Isolation, Synthesis, and Antioxidant Activity

Abstract: The chemical study of the bryozoan Schizomavella mamillata has led to the isolation of six new 5-alkylresorcinol derivatives, schizols A–F (1–6), whose structures were established by spectrocospic means. Schizol A (1) exhibits a (E)-6-phenylnon-5-enyl moiety linked to the C-5 of a resorcinol ring, while in schizol B (2) the substituent at C-5 contains an unusual 1,2-dihydrocyclobutabenzene moiety. Schizols C (3) and D (4) have been characterized as the 1-sulfate derivatives of 1 and 2, respectively, and schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Sulphate esters are common in marine natural products (sulphate esters within Marinlit marine natural products database: n = 1098) 50 . A number of studies have demonstrated various changes in biological activities of natural products due to variations in the number of sulphate esters [51][52][53][54][55][56][57] . At least one study comparing a class of marine natural products demonstrated a correlation between sulphate groups and reduced biological activity 49 , representing a detoxifying effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulphate esters are common in marine natural products (sulphate esters within Marinlit marine natural products database: n = 1098) 50 . A number of studies have demonstrated various changes in biological activities of natural products due to variations in the number of sulphate esters [51][52][53][54][55][56][57] . At least one study comparing a class of marine natural products demonstrated a correlation between sulphate groups and reduced biological activity 49 , representing a detoxifying effect.…”
Section: Resultsmentioning
confidence: 99%
“…At least one study comparing a class of marine natural products demonstrated a correlation between sulphate groups and reduced biological activity 49 , representing a detoxifying effect. Other studies have also demonstrated significant differences between sulphated and de-sulphated analogues of natural products, with many showing a decrease in biological activity for sulphate analogues [53][54][55] . Although a decrease in activity is common for sulphated derivatives, one study has described an increase in biological activity 57 , and another described an increase in activity for a disulphated analogue compared to its monosulphated counterpart 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Schizol A 1379 was synthesised from 3,5-dimethoxybenzaldehyde. 613 The Arctic species Securiustra securifrons yielded a number of halogenated alkaloids including securidine A 1385 (ref. 614) and securamines H 1386 and I 1387.…”
Section: Bryozoansmentioning
confidence: 99%
“…NH-F6 polyketides perylenequinones (294,295) [316]; sponge Petrosia alfiani xestoquinone derivatives petroquinones A and B (296, 297) [317]; fungus Peyronellaea glomerata isocoumarin derivatives peyroisocoumarins B and D (298,299) [318]; fungus Phoma sp. NTOU4195 polyketide phomaketide A (300) [319]; ascidian Sidnyum elegans phosphorylated polyketide phosphoeleganin (301) [320]; soft coral Pseudopterogorgia rigida sesquiterpenes (302, 303) [321]; sponge Spongia ceylonensis diterpene ent-13-norisocopalen-15-al-18-oic acid (304) [322]; bryozoan Schizomavella mamillata 5-alkylresorcinol derivatives schizols A and B (305, 306) [323]; fungus Stachybotrys longispora FG216 isoindolinone derivatives FGFC6 and FGFC7 (307,308) [324]; sponge Spongia pertusa Esper sesquiterpene (309) [325]; sponge Psammocinia sp. furanosesterterpene tetronic acid sulawesin A (310) [326]; cyanobacterium Okeania sp.…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%